Evidence for Trait Related Theory of Mind Impairment in First Episode Psychosis Patients and Its Relationship with Processing Speed: A 3 Year Follow-up Study - Ayesa-Arriola, Rosa; Setién-Suero, Esther; Neergaard, Karl D.; Ferro, Adele; Fatjó-Vilas, Mar; Ríos-Lago, Marcos; Otero, Soraya; Rodríguez-Sánchez, Jose M.; Crespo-Facorro, Benedicto (Frontiers in Psychology, 2016)
This study aimed to confirm whether first-episode psychosis patients present a stable trait impairment in theory of mind (ToM) and to examine the potential relationship between ToM and clinical symptomatology and neurocognition. Patients with a first episode of psychosis (N = 160) and healthy controls (N = 159) were assessed with an extensive neuropsychological test battery, which included a mental state decoding task known as “The Reading the Mind in the Eyes” (Eyes test), at baseline and reassessed after 1 and 3 years. The clinical group performed below healthy controls on the Eyes test while not showing test-retest differences between baseline and follow-up administrations. Analyses revealed age, education and premorbid IQ as potential moderators. Poorer performance on the Eyes test was not linked to clinical symptomatology but was associated with greater neurocognitive deficit, particularly related to processing speed. The persistence of ToM deficits in patients suggests that there are trait related mentalising impairments in first episode psychosis. This study shows the influence of processing speed and moderator variables on efficient ToM.